Cost analysis of facial injury treatment in two university hospitals in Malaysia: a prospective study - Sulong, Saperi; Ramli, Roszalina; Ahmed, Zafar; Muhd Nur, Amrizal; Ibrahim, Mohd Ismail; Rashdi, Muhd Fazlynizam; Nordin, Rifqah; Abd Rahman, Normastura; Yusoff, Azizah; Nazimi, Abd Jabar; Abdul Rahman, Roselinda; Abdul Razak, Noorhayati; et al. (Dove Medical Press, 2017)
Objective: Facial injury (FI) may occur in isolation or in association with injuries to other parts of the body (facial and other injury [FOI]). The objective of this study was to determine the direct treatment costs incurred during the management of facial trauma. Materials and methods: A prospective cohort study on treatment cost for FIs and FOIs due to road-traffic crashes in two university hospitals in Malaysia was conducted from July 2010 to June 2011. The patients were recruited from emergency departments and reviewed after 6 months from the date of initial treatment. Direct cost analysis, comparison of cost and length of hospital stay, and Injury Severity Score (ISS) were performed. Results: A total of 190 patients were enrolled in the study, of whom 83 (43.7%) had FI only, and 107 (56.3%) had FOI. The mean ISS was 5.4. The mean length of stay and costs for patients with FI only were 5.8 days with a total cost of US$1,261.96, whereas patients with FOI were admitted for 7.8 days with a total cost of US$1,716.47. Costs doubled if the treatment was performed under general anesthesia compared to local anesthesia. Conclusion: Treatment of FI and FOI imposes a financial burden on the health care system in Malaysia.